Post‐Synthetic Modification of Oligonucleotides Through Oxidative Amination of 4‐Thio‐2′‐Deoxyuridine. Issue 10 (13th October 2021) - Wang, Jingyi; Shang, Jiachen; Xiang, Yu; Tong, Aijun
Abstract: Functionalized oligonucleotides (ONs) are widely applied as target recognition molecules for biosensing and gene regulation. Herein, we describe a general method for post‐synthetic modification of ONs based on the oxidative amination of 4‐thio‐2′‐deoxyuridine (4SdU) with sodium periodate and several amines. Alkyne‐/azide‐, biotin‐, and fluorophore‐modified ONs were prepared by modifying 4SdU‐containing ONs with the corresponding amines and characterized for their bioorthogonal reactivity, streptavidin‐binding affinity, and fluorescence properties, respectively. We synthesized three fluorophore‐modified ONs with and without the aromatic fluorophores conjugated to modified nucleobases and investigated their emission properties. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Post‐synthetic modification of ONs Supporting Protocol : Preparation of dansyl ethylenediamine Basic Protocol 2 : Quantification of ON reaction yields Basic Protocol 3 : Characterization of modified ONs